Ex post evaluation of PPP government-led renegotiations: Impacts on the financing of road infrastructure. Issue 2 (3rd April 2019) - Fernandes, Carlos; Oliveira Cruz, Carlos; Moura, Filipe
Abstract: Renegotiations are often claimed to be the major pitfall in public–private partnership projects. In fact, the literature and empirical evidence suggest a bias toward favoring concessionaires, although there are well-known examples of harmful unilateral decisions by governments. This article establishes a distinction between structural renegotiations (with changes in the risk-sharing agreement) and nonstructural renegotiations (without shifting risk) and analyzes the implications of structural renegotiations in a road concession by comparing the ex ante and ex post financial implications for government, concessionaire, and users. The selected project is one that started as a shadow toll and was later changed to real toll. The analysis shows that the renegotiation essentially transferred costs to the users. The financial burden for the government decreased and the internal rate of return (IRR) of the concessionaire increased slightly although the overall risk profile of the concession decreased. The users supported a 40% higher cost, and the system gained an additional cost component (the electronic tolling system). Overall the global financial costs increased 40% when compared with the initial regime. The article also sets out some discussions and implications for policymakers.